2020
DOI: 10.1111/bcpt.13475
|View full text |Cite
|
Sign up to set email alerts
|

Actions of multiple doses of resveratrol on oxidative and inflammatory markers in plasma and brain of healthy and arthritic rats

Abstract: Chronic and systemic inflammation affecting the synovial membranes, articular cartilages and bones is the most evident symptom of rheumatoid arthritis. 1 The intense hyperplasia of the articular cartilage takes place with participation of T cells, B cells, macrophages, fibroblasts and pro-inflammatory cytokines, particularly interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and tumour necrosis factor alpha (TNFα). 2 Reactive oxygen species, however, also play an important role because the overproduction of pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…RES has been shown to have a broad range of neuroprotective effects in mammals; for example, Huang et al reported that RES could attenuate β-amyloid-induced neurotoxicity by suppressing inducible nitric oxide synthase production in adult rats [ 24 ]. Castro et al showed that RES also plays an important role in anti-oxidation and anti-inflammation in plasma and brain tissues [ 28 ]. Qian et al suggested that RES reduced brain edema and neuronal apoptosis in a subarachnoid hemorrhage rat model [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…RES has been shown to have a broad range of neuroprotective effects in mammals; for example, Huang et al reported that RES could attenuate β-amyloid-induced neurotoxicity by suppressing inducible nitric oxide synthase production in adult rats [ 24 ]. Castro et al showed that RES also plays an important role in anti-oxidation and anti-inflammation in plasma and brain tissues [ 28 ]. Qian et al suggested that RES reduced brain edema and neuronal apoptosis in a subarachnoid hemorrhage rat model [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sham group underwent surgical stress without MCAO or administration of any medication. After MCAO, in the vehicle control and resveratrol groups, vehicle (0.05 percent dimethyl sulfoxide (DMSO) in phosphate-buffered saline, Sigma-Aldrich, St. Louis, MO, USA) or 100 μl of a 135 mg/ml (13.5 mg/rat) resveratrol solution (∼50 mg/kg body weight, Sigma-Aldrich, St. Louis, MO, USA) [ 26 ] in 0.05 percent DMSO were inoculated through drip with a micropipette into each nostril of the rat for intranasal administration once a day for 7 consecutive days, while the rat was in the head-back supine position with a 70°–90° tilt to enhance drug absorption from the nasal cavity and facilitate uptake into the brain, while minimizing drainage into the esophagus and trachea ( Fig. 1 ) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%